Peningkatan Kompetensi Guru Melalui Pelatihan dan Pendampingan Pembuatan Media Pembelajaran Inovatif Berbasis Pembelajaran Daring - Ratna Widyastuti; Abidatul Izzah; Rinanza Zulmy Alhamri; Benni Agung Nugroho; Ellya Nurfarida (Jurnal Pengabdian pada Masyarakat Ilmu Pengetahuan dan Teknologi Terintegrasi, 2021)
The high interest of the students has motivated the teachers at SDN Dermo 1 to improve the quality of learning. Therefore, they initiate to create a learning media innovations such as manipulative media and computer media. However, building a learning innovations with computers-based was not accompanied by the abilities. To solve this problem, we hold community service activities that aimed to improve their capability in developing innovations by holding outreach on mathematics learning methods and training on implementing computer applications. The last step in this program is assistance in developing and implementing computer learning media in online course. Further, the Community Service Program named "Peningkatan Kompetensi Guru Melalui Pelatihan Dan Pendampingan Pembuatan Media Pembelajaran Inovatif Berbasis Pembelajaran Daring" was carried out in 5 stages of preparation, socialization, training, mentoring, and evaluation. Finally, this community service program has been produced a training module and teacher's capability more better. About the training modules, it can be used in online learning-based learning media. It started from the perception to evaluation stage. In fact, the learning methods that applied in SD Negeri 1 Dermo Kediri is on the track with Minister of Education and Culture's direction. Other than that, the training program can increase the quality of learning.